Cloacal gland, endocrine testicular, and adrenocortical photoresponsiveness in male Japanese quail exposed to short days - Busso, Juan Manuel (2013)
Photoperiod is the most important “noise-free” seasonal environmental cue for synchronizing physiological states (such as reproductive activity) in birds. However, in photoperiodic birds such as Japanese quail, the effect of photoperiod on adrenocortical activity remains unclear, particularly in males with differences in cloacal gland photoresponsiveness. At 8 wk of age, birds (n = 55) were either assigned to a short photoperiod (8L:16D; SD) or maintained under long photoperiod (16L:8D; LD; control). After 5 wk of SD exposure, males were classified as nonresponsive (SD-NR; with foam production) or responsive (SD-R; with no foam production) to short days, depending on the cloacal gland volume was above or below 1,000 mm3. At 14 wk of age, droppings were collected during 3 consecutive days to determine corticosterone (CMs) and androgen metabolites (AMs) by enzyme immunoassays. Male Japanese quail under LD showed significantly higher concentrations of CMs (300 ± 10 ng/g) and AMs (1,257 ± 115 ng/g) than birds kept under SD. Under short days, SD-NR and SD-R showed differences (P < 0.0001), both in CM (153 ± 8 ng/g and 98 ± 6 ng/g, respectively) and AM concentrations (1,294 ± 309 ng/g and 275 ± 53 ng/g, respectively). Interestingly, although SD-NR males exhibited no cloacal gland arrest (according to cloacal gland volume and foam production) and similar testicular activity (AM values) to LD males, they showed lower concentrations of CMs compared with males that remained on LD (P < 0.05). Our findings suggest length of photoperiod affected hypothalamic-pituitary-adrenal activity; however, that was not the only factor involved, because birds subjected to shorter days but whose hypothalamic-pituitary-gonadal axis failed to respond had intermediate CM values. Further research is required to elucidate the underlying mechanisms of this interesting finding.